Pediatric Pulmonology year in review 2018: Asthma, physiology/pulmonary function testing, and respiratory infections. Issue 10 (25th June 2019) - Loughlin, Ceila E.; Muston, Heather N.; Pena, Michael A.; Ren, Clement L.; Yilmaz, Ozge; Noah, Terry L.
Abstract: Pediatric Pulmonology publishes original research, reviews, and case reports related to a wide range of children's respiratory disorders. In our "Year in Review" series, we summarize publications in our major topic areas from 2018, in the context of selected literature in these areas from other journals relevant to our discipline. This review covers selected articles on asthma, physiology/lung function testing, and respiratory infections.